Improved microbial retting and quality jute (Corchorus spp.) fibre production in India – A review - MAJUMDAR, B; SAHA, A R; SARKAR, S; DATTA, S; MAZUMDAR, S P; SAHA, D; CHATTOPADHYAY, L; BARAI, S; KAR, G (The Indian Journal of Agricultural Sciences, 2022)
Jute (Corchorus spp. L.), the second most important fibre crop next to cotton, is a biodegradable and eco-friendly crop and one of the main cash crops of eastern India. India is the largest producer of raw jute in the world earning about `2200 crores per annum through export of diversified jute goods for which quality jute fibre is needed. The jute fibre quality depends directly on retting process. In India, more than 90% jute farmers do not have the access to free flowing water, so they carry out jute retting in stagnant water. The quality of jute fibre is deteriorated in stagnant water retting because of several factors like less rainfall, repeated retting, absence of efficient retting microbes, direct use of mud, soil etc. In this review paper we have discussed the views of various research workers about the efficient retting microbes, their utilization as microbial consortium for faster retting and quality jute fibre production even in stagnant water retting. Latest molecular approaches for identification of retting microbes including whole genome sequencing of retting microbes and their utilization as talc based formulation, spore based liquid formulation, use of immobilized strain of efficient retting microbes for faster environment friendly jute retting towards quality jute fibre production under farmers’ field conditions have also been discussed in detail.